Lead-free copper bismuth alloy material and preparation method and application thereof
By forming a metal plating layer on the bismuth surface and using foam copper-foamed copper-based three-dimensional network structure, the segregation problem of bismuth alloy material during sintering is solved, the strength and wear resistance of the material are improved, and its service life is extended.
Patent Information
- Application Number
- CN202510030539.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-18
AI Technical Summary
During the sintering process, the material strength is reduced due to the bismuth segregation phenomenon, and the wear resistance and adhesion resistance are insufficient, which affects its reliability and life in the friction pair.
The electroless plating process is used to form a metal plating layer on the bismuth surface to form a core-shell structure, and the three-dimensional network structure of foam copper is used as a continuous framework to enhance the structural stability and mechanical properties of the material.
It effectively prevents the mesh distribution of the bismuth phase along the grain boundary of the copper matrix during high-temperature sintering, enhances the strength and wear resistance of the material, and improves its use reliability and life in the friction pair.
Smart Images

Figure CN119843092A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of copper-based alloy materials, and in particular relates to a lead-free copper-bismuth alloy material and a preparation method and application thereof. Background Art
[0002] Metal-based solid self-lubricating materials have excellent properties such as high modulus, high strength and dimensional stability. At the same time, they also have good self-lubricating properties and can significantly improve the boundary lubrication characteristics of friction pairs. Lead-containing copper-based alloy materials such as CuSn10Pb10 or CuPb24Sn are widely used in various friction pair materials such as seals and bearings. However, lead-containing copper-based alloy materials are toxic, which not only pollutes the environment, but also seriously endangers human health. Therefore, lead is gradually replaced by other elements with similar lubrication properties and environmental friendliness.
[0003] Copper-bismuth self-lubricating alloy material is the preferred alloy material with good applicability and economy for mechanical equipment, and is also the preferred alloy material for replacing copper-lead alloy in friction pair materials. Copper-bismuth alloy is made by adding low-melting-point soft metal Bi to the copper matrix using powder metallurgy technology. Since bismuth metal has similar sliding characteristics to lead, the synthesized copper-bismuth material exhibits good friction reduction performance. However, copper-bismuth alloy belongs to a eutectic alloy. In the process of preparing copper-bismuth alloy using powder metallurgy technology, copper or copper alloy powder is usually directly mixed, pressed and sintered with bismuth powder. During the sintering process, the bismuth phase will have serious segregation phenomenon; bismuth is distributed in a network at the grain boundary of the copper alloy, which has a strong splitting and weakening effect on the copper matrix, thereby seriously weakening the strength of the copper-bismuth alloy material; at the same time, the network-distributed bismuth is also easy to fall off during the sliding friction process, reducing the wear resistance and anti-adhesion performance of the material, resulting in a significant reduction in the reliability and life of the copper-bismuth alloy material in the friction pair. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a lead-free copper-bismuth alloy material and its preparation method and application. The present invention uses a high-temperature resistant metal as a bismuth coating to improve the flow of the low-melting-point bismuth phase during the sintering process, forming a core-shell structure of the metal coating coating bismuth particles; effectively preventing the low-melting-point Bi phase from melting and distributing in a network along the grain boundary of the copper matrix during the high-temperature sintering process, thereby avoiding the strong splitting and weakening effect of the bismuth phase on the copper matrix phase; at the same time, using foam copper as a continuous skeleton and utilizing the three-dimensional network structure of foam copper, the continuity of the copper matrix and the core-shell structure during the sintering process is strengthened, thereby enhancing the performance of the copper-bismuth alloy material.
[0005] The first object of the present invention is to provide a method for preparing a lead-free copper-bismuth alloy material, comprising the following steps:
[0006] Step 1: modifying the surface of bismuth by chemical plating process to form a core-shell structure of bismuth coated with a metal plating layer, and obtaining a core-shell structure powder.
[0007] It should be noted that bismuth has a low melting point and good lubricity, so that it can provide a good friction reduction effect in the alloy. The present invention uses a chemical plating process to form a metal coating on the surface of bismuth, and the core-shell structure formed by the metal coating effectively covers the bismuth particles, thereby avoiding the low-melting point bismuth from penetrating into the copper matrix grain boundary during high-temperature sintering, thereby reducing its splitting and weakening effect on the matrix. Preferably, the metal coating is a nickel coating or a copper coating, and the thickness of the metal coating is 0.8μm to 1.5μm. Since the metal nickel has good compatibility with the copper matrix, it can also form a good metallurgical bond with the copper matrix. At the same time, the melting point of metal nickel is relatively high, and it will not melt during high-temperature sintering, and a stable shell layer can be formed to coat the bismuth particles. Moreover, the nickel coating can effectively block the penetration and network distribution of bismuth at high temperatures, and reduce the splitting effect of bismuth relative to the copper matrix. More preferably, the metal coating is a nickel coating.
[0008] It should also be noted that the specific preparation process of the core-shell structure powder of the present invention is as follows: Bi powder is added to a silver ammonia solution and a sodium hypophosphite solution in sequence for activation to obtain an activated Bi powder; under water bath heating conditions, the activated Bi powder is added to a metal plating solution, wherein the water bath temperature is 85°C to 95°C, so that the activated Bi powder undergoes an oxidation-reduction reaction with the metal plating solution, and no gas is generated in the solution, thereby obtaining a core-shell structure powder.
[0009] Preferably, the metal plating solution is a nickel plating solution or a copper plating solution. The specific preparation process of the nickel plating solution is: under stirring, pouring the nickel sulfate solution, the sodium hypophosphite solution and the thiourea solution into the sodium citrate solution in sequence to obtain a mixed solution; adding deionized water to dilute the mixed solution; then dripping the sodium hydroxide solution into the diluted mixed solution, adjusting the pH value to 10, and obtaining the nickel plating solution.
[0010] Step 2: Mix the copper matrix powder with the core-shell structure powder to obtain a mixed powder; use the foamed copper as a skeleton, add the mixed powder to the foamed copper, press and sinter, and use the three-dimensional network structure of the foamed copper to enhance the continuity between the copper matrix powder and the core-shell structure powder during the sintering process to obtain a lead-free copper-bismuth alloy material.
[0011] The present invention takes into account that the three-dimensional network structure of copper foam can provide a continuous copper matrix skeleton structure for the copper-bismuth alloy. Since the three-dimensional structure can evenly disperse stress, the local stress concentration phenomenon is greatly reduced, thereby ensuring the durability and fatigue resistance of the alloy; at the same time, the three-dimensional network can maintain the overall continuity of the copper matrix phase in the copper-bismuth alloy material, improve the overall structural stability of the copper-bismuth alloy, reduce the introduction of the low-melting-point bismuth phase on the overall fracture and weakening of the alloy material, and enhance the performance of the alloy material. In addition, the high thermal conductivity of copper foam helps it to evenly disperse heat during the sintering process, reduce heat accumulation, and thus avoid material performance degradation caused by local overheating during the sintering process.
[0012] It should be noted that the larger the pore size of the copper foam, the weaker the continuity of the three-dimensional network structure, and it is not easy to improve the overall splitting and weakening effect of the introduction of the low-melting-point bismuth phase on the alloy material. If the pore size of the copper foam is too small, it is not conducive to the flow and filling of the matrix powder and the core-shell structure powder inside it, which will reduce the density of the material and weaken the mechanical properties of the material. Preferably, the pore size of the copper foam is 10PPI to 50PPI.
[0013] It should also be noted that if the bismuth content in the copper-bismuth alloy is too high, the overall mechanical properties of the alloy material will be reduced; preferably, the content of the core-shell structure powder is less than 15% of the total mass of the lead-free copper-bismuth alloy.
[0014] Preferably, the matrix powder is spherical Cu powder or CuSn alloy powder, and the CuSn alloy is one of CuSn10, CuSn15 and CuSn20.
[0015] Preferably, the diameter of the spherical Cu powder or CuSn alloy powder is 30 μm to 150 μm.
[0016] In addition, sintering helps the evaporation or volatilization of moisture or organic matter inside the alloy material, the removal of adsorbed gas, the elimination of stress, the reduction of oxides on the surface of powder particles, the material migration between particles, recrystallization, grain growth, etc., thereby increasing the crystal contact surface between particles and shrinking or even eliminating pores. Preferably, the sintering conditions are sintering at a sintering temperature of 800°C to 900°C for 30min to 60min at a heating rate of 3°C to 6°C.
[0017] Preferably, the pressing pressure is 400 MPa to 500 MPa.
[0018] The second object of the present invention is to provide a lead-free copper-bismuth alloy prepared by the method for preparing the lead-free copper-bismuth alloy material.
[0019] The third object of the present invention is to provide application of the lead-free copper-bismuth alloy material in metal-based solid self-lubricating materials.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention uses a chemical plating process to modify the bismuth surface to form a core-shell structure in which bismuth is coated with a metal coating; the metal coating in the core-shell structure completely coats the bismuth particles, effectively isolating the bismuth particles from contact with the copper matrix during high-temperature sintering, thereby preventing the low-melting-point Bi phase from melting and distributing in a network along the grain boundaries of the copper matrix during high-temperature sintering, thereby avoiding the strong splitting and weakening of the bismuth phase on the copper matrix phase. In addition, the metal coating as a shell layer can maintain its shape and structural integrity at high temperatures, ensuring that the bismuth particles will not flow and redistribute due to melting at higher temperatures, and maintaining the structural stability of the copper-bismuth alloy. At the same time, the metal coating has good bonding with the copper matrix, which can improve the interface bonding strength between the core-shell structure alloy particles and the matrix, thereby improving the overall performance of the copper-bismuth alloy.
[0022] The present invention uses copper foam as a skeleton, adds a mixed powder of copper matrix powder and core-shell structure powder into the copper foam, and obtains a lead-free copper-bismuth alloy after pressing and sintering. The three-dimensional network of copper foam can provide internal support for the copper-bismuth alloy, maintain the overall continuity of the copper matrix phase in the copper-bismuth alloy material, improve the overall structural stability of the copper-bismuth alloy, reduce the cracking and weakening effect of the introduction of the low-melting-point bismuth phase on the overall alloy material, and enhance the performance of the alloy material. At the same time, because the three-dimensional structure of copper foam can evenly disperse stress, the local stress concentration phenomenon is greatly reduced, thereby ensuring the durability and fatigue resistance of the copper-bismuth alloy.
[0023] The preparation process of the invention is simple, the cost is low, and it is easy to implement and manufacture, and has a wide range of application value in friction pair components such as green new energy vehicles and sliding bearings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The microscopic SEM images of the bismuth powder of Example 1 of the present invention and a single bismuth particle in the core-shell structure powder prepared in Example 1; wherein (a) is the bismuth powder and (b) is the core-shell structure powder.
[0025] Figure 2 The SEM images of the microscopic distribution of Bi phase in the lead-free copper-bismuth alloy material prepared in Example 1 of the present invention; wherein (a) is the SEM image at 200 μm, and (b) is the local enlarged image in (a).
[0026] Figure 3 The SEM images of the microscopic distribution of Bi phase in the conventional copper-bismuth alloy material prepared in Comparative Example 1 of the present invention are shown; wherein (a) is the SEM image at 100 μm, and (b) is the local enlarged image in (a). DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings.
[0028] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.
[0029] Example 1
[0030] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0031] Step 1: Preparation of core-shell structure powder:
[0032] 1.1) 30 g of Bi powder was placed in 120 mL of anhydrous ethanol solution, cleaned in an ultrasonic cleaner for 20 min, filtered, and then placed in a vacuum drying oven at 60° C. for 2 h to obtain pretreated Bi powder.
[0033] 1.2) The pretreated Bi powder was added to a 2% silver ammonia solution, stirred for 60 minutes, filtered and dried; the dried Bi powder was then added to a 24 g / L sodium hypophosphite solution, stirred for 30 minutes, filtered, washed with deionized water 2 to 3 times, and dried for 2 hours to obtain activated Bi powder.
[0034] 1.3) Under stirring, pour 200 ml of 30 g / L nickel sulfate solution, 200 ml of 24 g / L sodium hypophosphite solution and 10 ml of 2 mg / L thiourea solution into 200 ml of 24 g / L sodium citrate solution to obtain a mixed solution; add deionized water to the mixed solution to dilute it to 1 L; then add 5 g / L sodium hydroxide solution dropwise to the diluted mixed solution, adjust the pH value to 10, and obtain a nickel plating solution.
[0035] 1.4) Adding activated Bi powder to the nickel plating solution under water bath heating conditions, wherein the water bath temperature is 90±2°C, and stirring continuously for 1 hour to obtain a reaction powder; filtering the reaction powder, rinsing with deionized water for 2 to 3 times, and then drying in a vacuum drying oven at 60°C for 4 hours to obtain a Ni@Bi core-shell structure powder.
[0036] Step 2: Preparation of lead-free copper-bismuth alloy material:
[0037] 2.1) Spherical CuSn10 powder with a diameter of 120 μm and core-shell structure powder are placed in a stirring powder mixer and mixed for 30 minutes to obtain a mixed powder; wherein the content of the core-shell structure powder is 6% of the total mass of the lead-free copper-bismuth alloy.
[0038] 2.2) Place the foam copper with a pore size of 10 PPI into a steel mold, and fix the mold on a vibration table to keep the vibration table working; wherein the power of the vibrator on the vibration table is 300 W, the amplitude is set to 0.3 mm, and the vibration frequency is 1000 times / min; slowly pour the mixed powder into the foam copper until the mixed powder is completely filled and spread in the foam copper skeleton to obtain a mixture.
[0039] 2.3) Place the mold containing the mixture on a press and maintain the pressure at 500 MPa for 10 seconds to obtain a green sample.
[0040] 2.4) placing the green sample in a high-temperature sintering furnace, sintering it at a sintering temperature of 900° C. for 60 min at a heating rate of 4° C., and obtaining a lead-free copper-bismuth alloy material after the sintering furnace is cooled to room temperature.
[0041] Example 2
[0042] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0043] The difference between this embodiment and embodiment 1 is:
[0044] In this embodiment, the pore size of the copper foam is 20 PPI.
[0045] Example 3
[0046] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0047] The difference between this embodiment and embodiment 1 is:
[0048] In this embodiment, the pore size of the copper foam is 30 PPI.
[0049] Example 4
[0050] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0051] The difference between this embodiment and embodiment 1 is:
[0052] In this embodiment, the pore size of the copper foam is 40 PPI.
[0053] Example 5
[0054] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0055] The difference between this embodiment and embodiment 1 is:
[0056] In this embodiment, the pore size of the copper foam is 50 PPI.
[0057] Example 6
[0058] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0059] The difference between this embodiment and embodiment 1 is:
[0060] The diameter of the spherical CuSn10 powder in this embodiment is 150 μm.
[0061] Example 7
[0062] This embodiment provides a method for preparing a lead-free copper-bismuth alloy material.
[0063] The difference between this embodiment and embodiment 1 is:
[0064] The diameter of the spherical CuSn10 powder in this embodiment is 30 μm.
[0065] Comparative Example 1
[0066] This comparative example provides a method for preparing a conventional copper-bismuth alloy material.
[0067] Copper powder and bismuth powder are weighed in a mass ratio of 47:3, and mixed evenly to obtain a mixed powder; the mixed powder is poured into a mold, and the pressure is maintained for 10 seconds at a pressure of 500 MPa to obtain a green body; the green body is placed in a high-temperature sintering furnace, and sintered at a sintering temperature of 900°C for 1 hour at a heating rate of 4°C, and after the sintering furnace is cooled to room temperature, a conventional copper-bismuth alloy material is obtained.
[0068] Comparative Example 2
[0069] This comparative example provides a method for preparing a lead-free copper-bismuth alloy material.
[0070] Step 1: Preparation of core-shell structure powder:
[0071] 1.1) 30 g of Bi powder was placed in 120 mL of anhydrous ethanol solution, cleaned in an ultrasonic cleaner for 20 min, filtered, and then placed in a vacuum drying oven at 60° C. for 2 h to obtain pretreated Bi powder.
[0072] 1.2) The pretreated Bi powder was added to a 2% silver ammonia solution, stirred for 60 minutes, filtered and dried; the dried Bi powder was then added to a 24 g / L sodium hypophosphite solution, stirred for 30 minutes, filtered, washed with deionized water 2 to 3 times, and dried for 2 hours to obtain activated Bi powder.
[0073] 1.3) Under stirring, pour 200 ml of 30 g / L nickel sulfate solution, 200 ml of 24 g / L sodium hypophosphite solution and 10 ml of 2 mg / L thiourea solution into 200 ml of 24 g / L sodium citrate solution to obtain a mixed solution; add deionized water to the mixed solution to dilute it to 1 L; then add 5 g / L sodium hydroxide solution dropwise to the diluted mixed solution, adjust the pH value to 10, and obtain a nickel plating solution.
[0074] 1.4) Adding activated Bi powder to the nickel plating solution under water bath heating conditions, wherein the water bath temperature is 90±2°C, and stirring continuously for 1 hour to obtain a reaction powder; filtering the reaction powder, rinsing with deionized water for 2 to 3 times, and then drying in a vacuum drying oven at 60°C for 4 hours to obtain a Ni@Bi core-shell structure powder.
[0075] Step 2: Preparation of lead-free copper-bismuth alloy material:
[0076] 2.1) Spherical CuSn10 powder with a diameter of 120 μm and core-shell structure powder were doped at a mass ratio of 47:3 and placed in a stirring powder mixer for mixing for 30 minutes to obtain a mixed powder.
[0077] 2.2) Pour the mixed powder into a mold, hold the pressure at 500 MPa for 10 seconds to obtain a green body; place the green body in a high-temperature sintering furnace, sinter at a sintering temperature of 900°C for 1 hour at a heating rate of 4°C, and after the sintering furnace is cooled to room temperature, a conventional copper-bismuth alloy material is obtained.
[0078] The difference between this comparative example and Example 1 is:
[0079] In this comparative example, the mixed powder is not filled in the copper foam.
[0080] Comparative Example 3
[0081] This comparative example provides a method for preparing a lead-free copper-bismuth alloy material.
[0082] Copper powder and bismuth powder were weighed at a mass ratio of 47:3, mixed evenly, and a mixed powder was obtained; a foam copper with a pore size of 10 PPI was placed in a steel mold, and the mold was fixed on a vibration table to keep the vibration table working; wherein, the power of the vibrator on the vibration table was 300 W, the amplitude was set to 0.3 mm, and the vibration frequency was 1000 times / min; the mixed powder was slowly poured into the foam copper until the mixed powder was completely filled and flattened in the foam copper skeleton to obtain a mixture. The mold containing the mixture was placed on a press, and the pressure was maintained for 10 seconds at a pressure of 500 MPa to obtain a green sample. The green sample was placed in a high-temperature sintering furnace, sintered at a sintering temperature of 900 ° C for 60 minutes at a heating rate of 4 ° C, and after the sintering furnace was cooled to room temperature, a lead-free copper-bismuth alloy material was obtained.
[0083] The difference between this embodiment and embodiment 1 is:
[0084] Bismuth powder is used in this embodiment.
[0085] Embodiments 1 to 7 of the present invention all produce lead-free copper-bismuth alloy materials that solve the problem of bismuth in copper-bismuth alloys splitting and weakening the copper matrix. The lead-free copper-bismuth alloy materials produced in Embodiments 1 to 7 and Comparative Examples 1 to 3 are used as examples for research. The specific research methods and results are as follows:
[0086] Experimental testing
[0087] 1. Surface morphology characterization
[0088] Figure 1 The following are microscopic SEM images of a single bismuth particle in the bismuth powder and the core-shell structure powder prepared in Example 1; wherein (a) is the bismuth powder and (b) is the core-shell structure powder. Figure 1 As can be seen from (a) in the figure, the surface of the bismuth powder particles is relatively smooth. Figure 1 As shown in (a), the surface of the bismuth particles in the core-shell structure powder formed after chemical plating is coated with a nickel-plated layer of tiny spherical particles with a small specific surface area and good stability.
[0089] Figure 2 The SEM images of the microscopic distribution of Bi phase in the lead-free copper-bismuth alloy material prepared in Example 1; wherein (a) is the SEM image at 200 μm, and (b) is the local magnified image in (a). Figure 2 As shown, after the core-shell structure is introduced, the bismuth particles are distributed in the copper matrix in the form of spherical dots, and nickel acts as a bridging element to form a dense bonding interface between the bismuth and the copper alloy matrix.
[0090] Figure 3 The SEM images of the microscopic distribution of Bi phase in the conventional copper-bismuth alloy material prepared in Comparative Example 1 are shown in FIG. 1 , wherein (a) is a SEM image at 100 μm, and (b) is a local magnified image of (a). Figure 3 It can be clearly seen that bismuth is distributed in a network-like manner in the copper alloy matrix along the copper alloy grain boundaries, and there are large gaps and holes between bismuth and the copper alloy matrix, which seriously splits and weakens the continuity of the copper matrix. Figure 2 Compared with the lead-free copper-bismuth alloy material prepared in Example 1, the present invention introduces a core-shell structure, and the nickel plating layer in the core-shell structure completely covers the bismuth particles. The covered bismuth particles are distributed in the copper matrix in a spherical point shape. Nickel acts as a bridging element to form a dense bonding interface between the bismuth and the copper alloy matrix, thereby effectively isolating the bismuth particles from contact with the copper matrix during high-temperature sintering, and avoiding the strong splitting and weakening of the bismuth phase on the copper matrix phase.
[0091] 2. Mechanical properties test
[0092] According to GB / T 232-2010 standard, the copper-bismuth alloy materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 are made into long strip specimens; wherein the size is 80mm×10mm×10mm; the long strip specimens are mounted on a bending tester, and a concentrated load is slowly applied at a loading speed of 1mm / min to 2mm / min to cause the specimens to undergo bending plastic deformation, and the bending strength of the materials is tested. The loading is continued until the specimens can no longer withstand the applied force, and the maximum force is recorded. The fracture toughness of the crack is calculated using the crack size and load data. The copper-bismuth alloy materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 are made into specimens; wherein the size of the specimens is 50mm×10mm×10mm; the impact toughness of the specimens is tested on a 300J pendulum impact tester. The copper-bismuth alloy materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were made into specimens; wherein the specimen dimensions were: inner and outer diameters were 15 mm and 25 mm, respectively, and a height was 15 mm; and the crushing strength of the ring specimens was tested by applying radial pressure on a WDW-100M universal electronic testing machine.
[0093] Table 1 Mechanical properties data of copper-bismuth alloys prepared in Examples 1 to 7 and Comparative Examples 1 to 3
[0094]
[0095] As can be seen from Table 1, with the increase of the pore size of the copper foam, from 10PPI to 50PPI, the mechanical properties of the lead-free copper-bismuth alloy material first gradually increase and then slightly decrease, but compared with the conventional copper-bismuth alloy material prepared in Comparative Example 1, the introduction of the three-dimensional network copper foam structure and the core-shell structure of the nickel-plated bismuth particles in the lead-free copper-bismuth alloy materials prepared in Examples 1 to 5 significantly improves the mechanical properties of the lead-free copper-bismuth alloy material; the copper foam skeleton with a pore size of 30PPI has a more significant improvement on the mechanical properties of the copper-bismuth alloy material. This shows that the three-dimensional network structure of the copper foam can improve the overall weakening effect of the introduction of the low-melting-point bismuth phase on the alloy material, improve the density of the material, and thus improve the mechanical properties of the material. Compared with the mechanical properties of the conventional copper-bismuth alloy material prepared in Comparative Example 1, the mechanical properties of the lead-free copper-bismuth alloy materials prepared in Examples 1 to 5 have been improved. At the same time, compared with the mechanical properties of the conventional copper-bismuth alloy material prepared in Comparative Example 1, the mechanical properties of the lead-free copper-bismuth alloy material prepared in Comparative Example 2, which only introduces the Ni@Bi core-shell structure, and Comparative Example 3, which only introduces the copper foam network structure, are also improved. This also shows that the present invention can hinder the expansion of low-melting-point bismuth in the copper alloy after melting during the sintering process of powder metallurgy materials by introducing a core-shell structure of bismuth particles coated with a nickel coating, and hinder the flow of low-melting-point bismuth phase in the copper powder after melting, so as to improve the characteristics of the network distribution of the bismuth phase along the grain boundary of the copper alloy, improve the strong splitting and weakening effect of the network distribution of the bismuth phase on the copper matrix, and thus play an effect of increasing the overall strength of the copper alloy matrix and the copper-bismuth alloy material. At the same time, the introduction of the three-dimensional network structure of the copper foam can enhance the continuity between the CuSn10 powder and the core-shell structure powder in the powder metallurgy process, reduce the splitting and weakening effect of the bismuth powder on the copper matrix, and strengthen the overall mechanical properties of the material.
[0096] As can be seen from Table 1, as the diameter of the spherical copper alloy powder decreases, the mechanical properties of the lead-free copper-bismuth alloy material also show a slight gradual improvement, which indicates that filling the raw copper alloy particles with a smaller particle size in the foam copper structure is conducive to the diffusion of atoms or molecules between the materials, thereby promoting the interface reaction and improving the alloy uniformity and mechanical properties of the material. Compared with the mechanical properties of the conventional copper-bismuth alloy material prepared in Comparative Example 1, the mechanical properties of the lead-free copper-bismuth alloy material prepared in the present invention are all improved.
[0097] 3. Friction performance test
[0098] The copper-bismuth alloy materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to tribological experiments on an M200 ring-block tribometer. The upper sample is a copper-bismuth alloy material, and the lower sample is a quenched 45 steel ring with a hardness of HRC53. The steel ring has a rotation sliding speed of 0.4 m / s. A load of 100N perpendicular to the upper sample is applied to the steel ring. The instantaneous friction coefficient is recorded using a ring-block sliding tribometer, and the average value is taken as the average friction coefficient of each sample. The wear rate of the copper-bismuth alloy material is calculated by testing the wear quality of the copper-bismuth alloy material before and after the experiment.
[0099] Table 2 Friction coefficient and wear rate of copper-bismuth alloy materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3
[0100]
[0101]
[0102] It can be seen from Table 2 that with the increase of the pore size of the copper foam, from 10PPI to 50PPI, the friction coefficient and wear rate of the lead-free copper-bismuth alloy material first gradually decrease and then slightly increase; the friction coefficient and wear rate of the copper foam skeleton with a pore size of 30PPI on the copper-bismuth alloy material are the lowest. Compared with the friction coefficient and wear rate of the conventional copper-bismuth alloy material prepared in Comparative Example 1, the friction coefficient and wear rate of the lead-free copper-bismuth alloy materials prepared in Examples 1 to 7 are both reduced. At the same time, compared with the friction coefficient and wear rate of the conventional copper-bismuth alloy material prepared in Comparative Example 1, the friction coefficient and wear rate of the lead-free copper-bismuth alloy material prepared in Comparative Example 2, which only introduces the Ni@Bi core-shell structure, and Comparative Example 3, which only introduces the copper foam network structure, are also reduced. This shows that the present invention introduces a core-shell structure of bismuth particles coated with a nickel plating layer and foamed copper as a continuous skeleton, and the nickel shell in the core-shell structure can solid dissolve with the copper matrix, thereby enhancing the interface bonding between the copper matrix and the bismuth phase, reducing the loss of the bismuth phase from the friction surface during sliding friction, exerting a good lubricating effect, and reducing the friction coefficient and wear rate of the copper-bismuth alloy material.
[0103] Compared with the mechanical properties of the conventional copper-bismuth alloy material prepared in comparative example 1, the crushing strength and impact toughness of the lead-free copper-bismuth alloy prepared in example 4 are increased by 46.5% and 52.8% respectively; the friction coefficient of the lead-free copper-bismuth alloy prepared in example 7 can be reduced by 24.7%, and the wear rate is reduced by 94.4%. The high-performance lead-free copper-bismuth alloy material prepared by the present invention not only conforms to the concept of green and sustainable development, but also can significantly improve the reliability and life of the friction pair, and has a wide range of application value in friction pair components such as new energy vehicles and sliding bearings.
[0104] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments, and these changes and modifications all fall within the scope of the present invention.
[0105] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a lead-free copper-bismuth alloy material, characterized in that: The following steps are involved: The bismuth surface is modified by chemical plating process to form a core-shell structure in which the bismuth is coated with a metal plating layer, thereby obtaining a core-shell structure powder; Copper matrix powder and core-shell structure powder are mixed to obtain mixed powder; using copper foam as a skeleton, the mixed powder is added to the copper foam, pressed and sintered, and the three-dimensional network structure of the copper foam is used to enhance the continuity between the copper matrix powder and the core-shell structure powder during the sintering process to obtain a lead-free copper-bismuth alloy material.
2. The method for preparing a lead-free copper-bismuth alloy material according to claim 1, characterized in that: The core-shell structure powder is prepared by the following steps: adding activated Bi powder to a metal plating solution under water bath heating conditions, wherein the temperature of the water bath is 85° C. to 95° C., so that the activated Bi powder and the metal plating solution undergo an oxidation-reduction reaction to obtain a core-shell structure powder; The metal plating solution is a nickel plating solution or a copper plating solution.
3. The method for preparing a lead-free copper-bismuth alloy material according to claim 2, characterized in that: The activated Bi powder is prepared by the following steps: adding the Bi powder to a silver ammonia solution and a sodium hypophosphite solution in sequence for activation to obtain an activated Bi powder; The concentration of the silver ammonia solution is 1% to 3%, and the concentration of the sodium hypophosphite solution is 22g / L to 26g / L.
4. The method for preparing a lead-free copper-bismuth alloy material according to claim 1, characterized in that: The metal plating layer is a nickel plating layer or a copper plating layer, and the thickness of the metal plating layer is 0.8 μm to 1.5 μm.
5. The method for preparing a lead-free copper-bismuth alloy material according to claim 1, characterized in that: The pore size of the foam copper is 10PPI-50PPI.
6. The method for preparing a lead-free copper-bismuth alloy material according to claim 1, characterized in that: The content of the core-shell structure powder is less than 15% of the total mass of the lead-free copper-bismuth alloy.
7. The method for preparing a lead-free copper-bismuth alloy material according to claim 1, characterized in that: The copper matrix powder is spherical Cu powder or CuSn alloy powder, and the diameter of the spherical Cu powder or CuSn alloy powder is 30 μm to 150 μm.
8. The method for preparing a lead-free copper-bismuth alloy material according to claim 1, characterized in that: The sintering conditions are: sintering at a sintering temperature of 800° C. to 900° C. for 30 min to 60 min at a heating rate of 3° C. to 6° C.
9. A lead-free copper-bismuth alloy material prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the lead-free copper-bismuth alloy material according to claim 9 in a metal-based solid self-lubricating material.